Composição e aspectos nutricionais da batata-doce (Ipomoea batatas (L.) Lam): revisão de literatura (Revista Brasileira Multidisciplinar, 2023)
Sweet potato is a different fiber, starch, vitamins and minerals, in addition to phytochemicals with antioxidant capacity, which can be a source of process, increasing or increasing its composition. This work aimed to obtain, through a bibliographic review, relevant data on the composition of different types of sweet potato, as well as on changes in the nutritional composition resulting from the use of some of its different forms of processing. For the articles, a search was carried out in electronic databases, including articles published in Portuguese, English and Spanish from 2000 and 2020. Initially, an analysis of the titles of the articles found was carried out, after years of selection those that do not include the pre-established criteria, as well as those that perform. Then, the abstracts were made, applying the reading of the inclusion and exclusion criteria, and, finally, a new selection by reading the articles in the integration. It was found that, among the different types of sweet potato analyzed, some revealed a high level of phenolic compounds at such levels of carotenoids and minerals, such as iron and potassium. An important case that has been extensively investigated in other studies concerns the changes introduced in thermal processing, which can increase or reduce the nutritional parameters presented in sweet potatoes, such as phenolic compounds and beta-carotene. Therefore, it is of great importance to understand how these techniques interfere in the nutritional composition, in order to avoid the nutritional composition, as well as to allow better choices of the cooking methods used.
Keywords: foods; antioxidant; roots; nutrients.